2015
DOI: 10.1063/1.4921577
|View full text |Cite
|
Sign up to set email alerts
|

The effect of copper on the sub-bandgap density of states of CdTe solar cells

Abstract: Two optical sub-bandgap transitions in CdTe thin-film solar cells have been identified using detailed transient photocapacitance and transient photocurrent spectroscopy measurements. A broad response centered at EV + 0.9 eV directly correlates with the quantity of Cu present in the absorber layer, while a second response at EV + 1.2 eV does not depend on Cu or Zn and may be an intrinsic defect. These results demonstrate the influence of Cu on the sub-bandgap density of states of CdTe, and they are critical to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Urbach energies from CH 3 NH 3 Pb(I 1−x Br x ) 3 perovskites in this study are shown as red squares, and those from literature data are shown as blue triangles. 11,14 Also shown are a range of technologically important semiconductors (black dots): CZTSSe (Se-rich Cu 2 ZnSn(S,Se) 4 ),20 Si, 10 CIGS (Cu(In,Ga)Se 2 ),19 InP,29 GaAs, 30 CdTe,31 CZTS (S-rich Cu 2 ZnSnS 4 ),20 CGS (CuGaSe 2 ), 32 a-Si, 33 a-SiC:H,34 Al 0.05 In 0.95 N,35 and In x Ga 1−x N (In-rich, graded In profile).36…”
mentioning
confidence: 99%
“…Urbach energies from CH 3 NH 3 Pb(I 1−x Br x ) 3 perovskites in this study are shown as red squares, and those from literature data are shown as blue triangles. 11,14 Also shown are a range of technologically important semiconductors (black dots): CZTSSe (Se-rich Cu 2 ZnSn(S,Se) 4 ),20 Si, 10 CIGS (Cu(In,Ga)Se 2 ),19 InP,29 GaAs, 30 CdTe,31 CZTS (S-rich Cu 2 ZnSnS 4 ),20 CGS (CuGaSe 2 ), 32 a-Si, 33 a-SiC:H,34 Al 0.05 In 0.95 N,35 and In x Ga 1−x N (In-rich, graded In profile).36…”
mentioning
confidence: 99%
“…Warren et al reaffirmed the results with the time-of-flight secondary-ion mass spectrometry (SIMS). 56 When the amount of Cu exceeds the threshold level, it leads to the formation of substitutional complexes Cu Cd − and interstitial defect Cu i 2+ , which have been reported many times previously. The diffusion of Cu creates defects leading to crossover by reducing the lifetime of photogenerated charge carriers.…”
Section: Back Contactmentioning
confidence: 74%
“…The greater concentration of Cu Cd will improve the hole concentration and hence the p-type conductivity of the CdTe device. Warren et al reaffirmed the results with the time-of-flight secondary-ion mass spectrometry (SIMS) …”
Section: Back Contactmentioning
confidence: 99%
“…Values reported for CIGS, range from 18 to 26 meV, for CdTe from 15 to 25 meV, and for CZTS from 13 to 31 meV. [27][28][29][30] At energies below the bandtail, the spectra of both samples are well fitted by the sum of two defect transitions occurring at 0.64 and 1.10 eV. For the sample without hydrogenation, the defect transition at 1.10 eV dominates the sub-gap absorption.…”
Section: -34mentioning
confidence: 99%
“…TPI spectroscopy, a form of sub-gap absorption spectroscopy, was used to characterize the energetic distribution of optically active defects in the band gap of TF-VLS InP photovoltaic devices. 27,28 In order to measure a TPI spectrum, a current transient was produced by holding the sample in reverse bias (-0.5 V) following a 100 ms filling pulse (+0.2 V). The samples were illuminated with monochromatic light during every other transient, and the TPI signal was calculated from the integrated difference between the illuminated and nonilluminated transients.…”
Section: -26mentioning
confidence: 99%